Acrylic resin loaded zero-valent iron material as well as preparation method and application method thereof
By combining acrylic resin-loaded zero-valent iron material with anaerobic sludge, the problems of long doubling time of anaerobic ammonia oxidizing bacteria and the generation of by-product nitrate nitrogen are solved, and more efficient nitrogen removal effect and better water effluent quality are achieved.
Patent Information
- Application Number
- CN202411870132.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-18
AI Technical Summary
The doubling time of anaerobic ammonia oxidizing bacteria is long, resulting in a long process start-up cycle, and the production of by-product nitrate nitrogen affects the quality of the effluent.
A resin that can be loaded with zero-valent iron is prepared by acidification treatment, reduction treatment and soaking treatment, and a resin material that can be loaded with zero-valent iron is prepared, and combined with anaerobic sludge for anaerobic ammonia oxidation treatment.
The doubling time of anaerobic ammonia oxidizing bacteria is shortened, the activity and system denitrification efficiency of anaerobic ammonia oxidizing bacteria are improved, the production of by-product nitrate nitrogen is reduced, and the effluent quality is improved.
Smart Images

Figure CN119660955A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of biological denitrification of sewage, and more specifically to an acrylic resin-loaded zero-valent iron material and a preparation method and an application method thereof. Background Art
[0002] Anaerobic ammonium oxidation is a biological reaction process in which anaerobic ammonium-oxidizing bacteria use ammonia nitrogen as an electron donor and nitrite nitrogen as an electron acceptor to generate nitrate nitrogen and nitrogen gas under anaerobic or anoxic conditions. Compared with the traditional nitrification-denitrification nitrogen removal process, anaerobic ammonium oxidation technology can effectively reduce the demand for organic matter and sludge production, reduce the generation of greenhouse gases, and can become one of the sustainable wastewater treatment methods.
[0003] However, the doubling time of anaerobic ammonium oxidizing bacteria is relatively long, and microorganisms are easily lost with the effluent, resulting in a long process startup cycle. In addition, since nitrite nitrogen is prone to redox reactions in water bodies, it cannot exist stably for a long time. At the same time, a small amount of byproduct nitrate nitrogen will be produced during the anaerobic ammonium oxidation reaction, affecting the effluent. Summary of the invention
[0004] 1. Technical problem to be solved by the invention
[0005] In view of the shortcoming that the doubling time of anaerobic ammonium oxidizing bacteria in the anaerobic ammonium oxidizing process in the prior art is long, an acrylic resin-loaded zero-valent iron material and an application method are provided to shorten the doubling time of anaerobic ammonium oxidizing bacteria and improve the activity of anaerobic ammonium oxidizing bacteria and the denitrification efficiency of the system.
[0006] 2. Technical solution
[0007] In order to achieve the above object, the technical solution provided by the present invention is:
[0008] An acrylic resin-loaded zero-valent iron material of the present invention,
[0009] The acrylic resin loaded zero-valent iron material comprises an acrylic cation exchange resin, and the acrylic cation exchange resin is loaded with zero-valent iron.
[0010] The present invention also provides a method for preparing the above-mentioned acrylic resin-loaded zero-valent iron material, comprising the following steps:
[0011] S1. Acidification treatment of acrylic acid type cation exchange resin;
[0012] S2. FeCl3·6H2O, acidified acrylic acid cation exchange resin and polyvinyl pyrrolidone are added to solvent A for mixing;
[0013] S3. The mixed acrylic acid cation exchange resin is reduced by a reducing agent to obtain an acrylic acid resin loaded with zero-valent iron material;
[0014] S4. Soaking the acrylic resin-loaded zero-valent iron material in a NaCl aqueous solution.
[0015] Furthermore, in step S1, the acrylic acid type cation exchange resin includes a macroporous weakly acidic acrylic acid cation exchange resin.
[0016] Preferably, the acrylic acid type cation exchange resin is a macroporous weakly acidic acrylic acid cation exchange resin.
[0017] Furthermore, the models of the macroporous weakly acidic acrylic cation exchange resin include D152.
[0018] Furthermore, in step S1, the acidification treatment includes treatment with hydrochloric acid.
[0019] It should be noted that the acidification treatment is to remove the Na + Exchange to H + .
[0020] Furthermore, the concentration of the hydrochloric acid may be 3-4 mol / L.
[0021] Furthermore, in step S1, the acidification treatment time is 1 to 2 hours.
[0022] Furthermore, after the acidification treatment, the process further comprises: washing with distilled water.
[0023] Furthermore, in step S2, the mass ratio of the FeCl3·6H2O, the acidified acrylic acid type cation exchange resin and polyvinyl pyrrolidone is 1:5:(0.2-0.4).
[0024] Furthermore, in step S2, the mixing treatment time is 10 to 12 hours.
[0025] It should be noted that the mixing time should be controlled to ensure that all Fe 3+ Exchanged to the surface of acrylic acid type cation exchange resin.
[0026] Furthermore, the mixing treatment further comprises: washing with distilled water to remove the unexchanged Fe 3+ .
[0027] Furthermore, the mixing process may be performed by magnetic stirring.
[0028] Furthermore, in step S2, the solvent A is distilled water.
[0029] Furthermore, in step S3, the reducing agent is one of a NaBH4 solution and a NaBH3CN solution.
[0030] Specifically, the concentration of the NaBH4 solution can be 0.01 to 0.1 mol / L.
[0031] Furthermore, the step S3 is specifically as follows:
[0032] Putting the mixed acrylic acid type cation exchange resin into distilled water;
[0033] While stirring, slowly add the reducing agent under inert gas purge and continue stirring for 2 to 3 hours.
[0034] Furthermore, the inert gas may be one or both of nitrogen and argon; the inert gas is preferably nitrogen.
[0035] Furthermore, after the reduction treatment, the reduction treatment further includes: washing with distilled water to remove unreacted reducing agent on the surface, such as NaBH4 solution.
[0036] Furthermore, in step S4, the soaking treatment time is 30 to 60 minutes.
[0037] The -OH in the acrylic acid type cation exchange resin is converted to -Cl by soaking treatment, thereby avoiding pH changes caused by -OH exchange.
[0038] Furthermore, in step S4, the mass concentration of the NaCl aqueous solution is 5% to 10%.
[0039] The present invention also provides an application method of the above-mentioned acrylic resin-loaded zero-valent iron material coupled with anaerobic ammonia oxidation nitrogen removal, comprising:
[0040] Using the acrylic resin loaded zero-valent iron material and anaerobic sludge to perform anaerobic ammonia oxidation treatment on wastewater;
[0041] Wherein, the mass ratio of the acrylic resin loaded zero-valent iron material to the anaerobic sludge is 3 to 6:1;
[0042] The hydraulic retention time of the wastewater is 6 to 12 hours.
[0043] Furthermore, the sludge concentration of the anaerobic sludge is 4000-6000 mg / L.
[0044] Furthermore, the concentration of ammonia nitrogen in the wastewater is 100-500 mg / L.
[0045] Furthermore, the acrylic resin-loaded zero-valent iron material and anaerobic sludge are added to an anaerobic reactor to perform anaerobic ammonia oxidation treatment on wastewater.
[0046] Furthermore, the anaerobic sludge contains anaerobic ammonium-oxidizing bacteria.
[0047] 3. Beneficial effects
[0048] Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects:
[0049] In the application method of the acrylic resin-loaded zero-valent iron material coupled with anaerobic ammonium oxidation nitrogen removal provided by the present invention, the acrylic cation exchange resin in the acrylic resin-loaded zero-valent iron material not only serves as an enrichment carrier for anaerobic ammonium oxidizing bacteria, but also serves as an electron shuttle to promote the microbial electron transfer process. The iron element plays a vital role in the synthesis of Fe-S protein and heme C of anaerobic ammonium oxidizing bacteria. Therefore, the acrylic resin-loaded zero-valent iron material will play a synergistic role in anaerobic ammonium oxidation, accelerate the start-up of anaerobic ammonium oxidation, and further improve the denitrification performance of anaerobic ammonium oxidation. It can also reduce the production of byproduct nitrate nitrogen and improve the effluent quality. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] Figure 1 This is a wastewater treatment system used in the application example of the present invention.
[0051] Explanation of the symbols in the schematic diagram:
[0052] 100. water inlet tank; 200. peristaltic pump; 300. UASB reactor; 400. water outlet tank; 500. air bag. DETAILED DESCRIPTION
[0053] The present disclosure may be more easily understood by reference to the following description in conjunction with examples, all of which constitute a part of the present disclosure. It should be understood that the present disclosure is not limited to the specific products, methods, conditions or parameters described and / or illustrated herein. Further, the terms used herein are only used for the purpose of describing specific embodiments by way of example and are not intended to be limiting unless otherwise indicated.
[0054] It should also be understood that, for the sake of clarity, certain features of the present disclosure may be described herein in the context of separate embodiments, but may also be provided in combination with each other in a single embodiment. That is, unless clearly incompatible or specifically not included, each separate embodiment is considered to be combinable with any other embodiment, and the combination is considered to represent another different embodiment. Conversely, for the sake of simplicity, the various features of the present disclosure described in the context of a single embodiment may also be provided individually or in any sub-combination. Finally, although a particular embodiment may be described as part of a series of steps or part of a more general structure, each step or substructure itself may also be considered to be an independent embodiment.
[0055] Unless otherwise indicated, it should be understood that each individual element in a list and each combination of individual elements in the list will be interpreted as a different embodiment. For example, a list of embodiments represented as "A, B, or C" should be interpreted to include embodiments "A", "B", "C", "A or B", "A or C", "B or C", or "A, B, or C".
[0056] In general, the use of the term "about" indicates an approximate value that can vary depending on the desired properties obtained by the disclosed subject matter, and will be interpreted in a context-dependent manner based on function. Therefore, one of ordinary skill in the art will be able to interpret a certain degree of difference on a case-by-case basis. In some cases, the number of significant figures used when expressing a particular value can be a representative technique for determining the difference allowed by the term "about". In other cases, a gradient in a range of values can be used to determine the range of differences allowed by the term "about". Further, all ranges in this disclosure are inclusive and combinable, and reference to a value in a range includes each value within that range.
[0057] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the invention belongs; the terms used herein and / or include any and all combinations of one or more of the associated listed items.
[0058] In the following examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if no manufacturer is specified, are all conventional products that can be purchased commercially.
[0059] The acrylic acid type cation exchange resin used in the embodiment of the present invention is a macroporous weakly acidic acrylic acid cation exchange resin purchased from Beijing Wokai Biotechnology Co., Ltd., model D152.
[0060] The present invention is further described below in conjunction with specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art. The essential characteristics and remarkable effects of the present invention can be reflected from the following examples, and the described embodiments are part of the embodiments of the present invention, rather than all the embodiments, and therefore, they do not limit the present invention in any way, and those skilled in the art make some non-essential improvements and adjustments based on the content of the present invention, which all belong to the protection scope of the present invention.
[0061] Example 1
[0062] This embodiment prepares an acrylic resin-loaded zero-valent iron material, and the specific steps include:
[0063] (1) First, 150 g of acrylic acid type cation exchange resin was selected, and the acrylic acid type cation exchange resin was treated with 4 mol / L hydrochloric acid for 2 hours, and then cleaned with distilled water;
[0064] (2) 30 g of FeCl3·6H2O was mixed with the treated resin in 1000 mL of distilled water, and then 6 g of polyvinyl pyrrolidone was added dropwise. The mixture was stirred magnetically for 12 hours and then washed with distilled water;
[0065] (3) The resin in step (2) was transferred into 1000 mL of distilled water, and 500 mL of 0.02 mol / L NaBH4 solution was slowly added under magnetic stirring and nitrogen purge, and stirred for 3 hours. Finally, the black resin was washed with distilled water and soaked in a 5% NaCl aqueous solution for 30 minutes to finally obtain an acrylic resin-loaded zero-valent iron material.
[0066] Example 2
[0067] This embodiment prepares an acrylic resin-loaded zero-valent iron material, and the specific steps include:
[0068] (1) First, 150 g of acrylic acid type cation exchange resin was selected and treated with 3 mol / L hydrochloric acid for 2 hours, and then washed with distilled water;
[0069] (2) 30 g of FeCl3·6H2O was mixed with the treated resin in 1000 mL of distilled water, and then 12 g of polyvinyl pyrrolidone was added dropwise. The mixture was stirred magnetically for 10 hours and then washed with distilled water;
[0070] (3) The resin in step (2) was transferred into 1000 mL of distilled water, and 500 mL of 0.1 mol / L NaBH4 solution was slowly added under magnetic stirring and nitrogen purge, and stirred for 3 hours. Finally, the black resin was washed with distilled water and soaked in a 10% NaCl aqueous solution for 60 minutes to finally obtain an acrylic resin-loaded zero-valent iron material.
[0071] Example 3
[0072] This embodiment prepares an acrylic resin-loaded zero-valent iron material, and the specific steps include:
[0073] (1) First, 150 g of acrylic acid type cation exchange resin was selected and treated with 4 mol / L hydrochloric acid for 1 hour, and then washed with distilled water;
[0074] (2) 30 g of FeCl3·6H2O was mixed with the treated resin in 1000 mL of distilled water, and then 9 g of polyvinyl pyrrolidone was added dropwise. The mixture was stirred magnetically for 10 hours and then washed with distilled water;
[0075] (3) The resin in step (2) was transferred into 1000 mL of distilled water, and 500 mL of 0.1 mol / L NaBH4 solution was slowly added under magnetic stirring and nitrogen purge, and stirred for 3 hours. Finally, the black resin was washed with distilled water and soaked in a 5% NaCl aqueous solution for 30 minutes to finally obtain an acrylic resin-loaded zero-valent iron material.
[0076] Application Examples
[0077] (1) The experimental group was divided into two groups, namely, a group in which the acrylic resin loaded zero-valent iron material prepared in Example 1 was added and a group without addition, namely, a blank control group (Comparative Application Example 1). Figure 1 The wastewater treatment system shown in the figure, wherein the selected anaerobic reactor is a UASB reactor 300 (with a built-in three-phase separator), with a volume of 5L, and each reactor is inoculated with 27g of anaerobic sludge specially cultivated in the laboratory (sludge concentration is 6000mg / L). The resin-loaded zero-valent iron material prepared in Example 1 is added at a ratio of 4g of material per gram of sludge.
[0078] (2) Ammonia nitrogen and nitrite nitrogen in wastewater are provided in the form of (NH4)2SO4 and NaNO2, with influent concentrations of 100 mg / L and 110 mg / L, respectively. Other solution compositions: KH2PO4 (10 mg / L), CaCl2·2H2O (6 mg / L), MgSO4·7H2O (300 mg / L), FeSO4·7H2O (6 mg / L), EDTA (6 mg / L), and NaHCO3 (60 mg / L).
[0079] (3) The wastewater in the water inlet tank 100 is fed into the bottom of the UASB reactor 300 through a peristaltic pump 200, and the hydraulic retention time is controlled at 8 hours. The mud-water mixture is separated by a three-phase separator, and the effluent enters the water outlet tank 400. The generated waste gas is discharged through the pipe at the top of the reactor and collected by the air bag 500, i.e., an ordinary plastic bag; the sludge and filler are trapped in the reactor. The UASB reactor 300 is provided with an external circulation through a peristaltic pump 200 and a pipe, which plays a role in fully mixing the mud and water and increasing the pollutant removal effect.
[0080] (3) Results: The experiment was carried out for 7 days, and samples were taken every day to measure the nitrate nitrogen and ammonia nitrogen content. The results of the sampling on the last day of the experiment showed that the ammonia nitrogen removal rate of the blank control group was 88%, and the nitrite nitrogen removal rate was 84%; the ammonia nitrogen removal rate of the resin zero-valent iron group was 90%, and the nitrite nitrogen removal rate was 93%. The above results show that the addition of acrylic resin loaded zero-valent iron material helps to improve the anaerobic ammonia oxidation capacity and enhance the removal effect of nitrogen in the water body.
Claims
1. An acrylic resin loaded zero-valent iron material, characterized in that: The acrylic resin loaded zero-valent iron material comprises an acrylic cation exchange resin, and the acrylic cation exchange resin is loaded with zero-valent iron.
2. A method for preparing the acrylic resin-loaded zero-valent iron material according to claim 1, characterized in that: The following steps are involved: S1. Acidification treatment of acrylic acid type cation exchange resin; S2. FeCl3·6H2O, acidified acrylic acid cation exchange resin and polyvinyl pyrrolidone are added to solvent A for mixing; S3. The mixed acrylic acid cation exchange resin is reduced by a reducing agent to obtain an acrylic acid resin loaded with zero-valent iron material; S4. Soaking the acrylic resin-loaded zero-valent iron material in a NaCl aqueous solution.
3. The method for preparing the acrylic resin-loaded zero-valent iron material according to claim 2, characterized in that: In step S1, the acrylic acid type cation exchange resin includes a macroporous weakly acidic acrylic acid series cation exchange resin.
4. The method for preparing the acrylic resin-loaded zero-valent iron material according to claim 3, characterized in that: In step S2, the mass ratio of the FeCl3·6H2O, the acidified acrylic acid type cation exchange resin and polyvinyl pyrrolidone is 1:5:(0.2-0.4).
5. The method for preparing the acrylic resin-loaded zero-valent iron material according to claim 4, characterized in that: In step S2, the mixing treatment time is 10 to 12 hours.
6. The method for preparing the acrylic resin-loaded zero-valent iron material according to claim 5, characterized in that: In step S1, the acidification treatment includes treatment with hydrochloric acid; and / or, In step S1, the acidification treatment is carried out for 1 to 2 hours.
7. The method for preparing an acrylic resin-supported zero-valent iron material according to any one of claims 2 to 6, characterized in that: In step S3, the reducing agent is one of NaBH4 solution and NaBH3CN solution.
8. The method for preparing the acrylic resin-loaded zero-valent iron material according to claim 7, characterized in that: In step S4, the soaking treatment time is 30 to 60 minutes; and / or, In step S4, the mass concentration of the NaCl aqueous solution is 5% to 10%.
9. A method for using the acrylic resin-loaded zero-valent iron material according to claim 1 or the acrylic resin-loaded zero-valent iron material prepared by the preparation method according to any one of claims 2 to 8 coupled with anaerobic ammonia oxidation for nitrogen removal, characterized in that: include: Using the acrylic resin loaded zero-valent iron material and anaerobic sludge to perform anaerobic ammonia oxidation treatment on wastewater; Wherein, the mass ratio of the acrylic resin loaded zero-valent iron material to the anaerobic sludge is 3 to 6:1; The hydraulic retention time of the wastewater is 6 to 12 hours.
10. The application method of acrylic resin loaded zero-valent iron coupled anaerobic ammonium oxidation nitrogen removal according to claim 9, characterized in that: The sludge concentration of the anaerobic sludge is 4000-6000 mg / L; The concentration of ammonia nitrogen in the wastewater is 100-500 mg / L.
Citation Information
Patent Citations
Zero-valent iron-carrying nano compound resin for catalyzing and degrading pollutant and preparation method
CN101474560A
Preparation method for polystyrene-resin-loaded nano zero valent iron, and application of polystyrene-resin-loaded nano zero-valent iron to oily wastewater
CN102489267A
Water treatment device and method with strengthened anaerobic ammonia oxidation
CN113044976A
Method for realizing high-efficiency treatment of low-nitrogen load wastewater by anaerobic ammonia oxidation system by adding modified charcoal
CN117819710A
Apparatus and method for reducing nitrate using iron-oxidizing microorganism
US20140138311A1